PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA SISWA KELAS IV SDN 021 SAMARINDA UTARA - Nurul Hikmah (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
This study aims to know to know the Improvement of Learning Outcomes About Style Through Model Learning Snowball Throwing In Students Class IV SDN 021 North Samarinda. The type of this research is Classroom Action Research (PTK), which is implemented in SDN 021 North Samarinda precisely in class IV which amounts to 17 students. Data collection techniques used in this study is the observation sheet of teacher and student activity when the learning process, written test, documentation. The study was conducted with two cycles and each cycle consisted of two meetings, each cycle consisting of four stages, namely planning, implementation, observation and reflection. Based on the observation data obtained in each cycle, can be seen the student learning outcomes increase well. The results showed that through the model of learning Snowball Throwing can improve student learning outcomes. Improvement of student learning outcomes from prasiklus of 41.2% with an average value of 50.29 subsequently increased in the first cycle of 76.47% with an average value of 70.58. Then on the second cycle has increased 88.23% with an average student 80.58. By applying the Snowball Throwing learning model can increase student activity in teaching and learning process, this can be seen with the increase in each cycle. The percentage in prasiklus is 49.99%. Next cycle I is 72.05%, the percentage in cycle II is 85.29%. The conclusion in this research by using Snowball Throwing learning model can improve learning result and student activity of Class IV SDN 021 North Samarinda.